PUBLIC KNOWLEDGE, ATTITUDES, AND ACCESS TO INFORMATION MEDIA TOWARDS WASTE MANAGEMENT IN JUANG CITY - Rizal Saputra; Sitti Zubaidah; Ernawita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Domestic waste management requires active community involvement supported by adequate levels of knowledge, attitudes, and access to information. This study aims to describe the level of community knowledge, attitudes, and access to information media regarding waste management in Kota Juang District, Bireuen Regency. The study used a descriptive quantitative approach with a cross-sectional design. A total of 120 respondents were selected using an accidental sampling technique. Data collection was conducted through structured questionnaires, field observations, and documentation studies. Data were analyzed descriptively using frequency distributions, percentages, and average values. The results showed that the level of community knowledge was in the moderate category, especially still low in technical aspects of waste management such as waste classification, transportation schedules, and the application of the 3R principle ( Reduce, Reuse, Recycle ). Community attitudes towards waste management were relatively positive, indicated by high concern for environmental cleanliness and support for shared responsibility in waste management. Meanwhile, community access to information media was in the high category, with social media and government websites being the most widely accessed and effective sources of information. This study concluded that the community in Kota Juang District has quite good social readiness in supporting community participation-based waste management. However, it is necessary to strengthen technical education, optimize digital-based environmental communication, and increase community participation to support more sustainable waste management .